Cu2O templating strategy for the synthesis of octahedral Cu2O@Mn(OH)2 core–shell hierarchical structures with a superior performance supercapacitor. Issue 28 (27th June 2018) - Guan, Hongtao; Cai, Pan; Zhang, Xiaomeng; Zhang, Yanlin; Chen, Gang; Dong, Chengjun
Abstract : We demonstrate the design and fabrication of novel Cu2 O@Mn(OH)2 core–shell hierarchical structures using octahedral Cu2 O as a template. Abstract : We demonstrate the design and fabrication of novel Cu2 O@Mn(OH)2 core–shell hierarchical structures using octahedral Cu2 O as a template. The Cu2 O backbone supports the growth of an ultrathin Mn(OH)2 nanoflake shell, leading to a relatively large surface area (65.8 m 2 g −1 ) for sufficient utilization of active materials. Cyclic voltammetry (CV) and galvanostatic charge–discharge measurements (GCD), as well as cycling stability and electrochemical impedance spectroscopy (EIS) were performed to examine the electrochemical performances of the Cu2 O@Mn(OH)2 core–shell structure. Applied as a supercapacitor electrode, the Cu2 O@Mn(OH)2 composite delivers a high specific capacitance of 540.9 F g −1 at 1 A g −1 and an energy density of 6.4–18.2 Wh kg −1 . After conducting 3000 cycles at 5.0 A g −1, the capacitance retention of 71.5% was achieved. The unique core–shell structure of the Cu2 O@Mn(OH)2 composite favours the effective transport of electrolytes and shortens the ion diffusion path. In addition, the synergetic effects from both Cu2 O and Mn(OH)2 significantly enhance the electrochemical performances. Our findings suggest that this Cu2 O@Mn(OH)2 core–shell is very promising for next generation high-performance supercapacitors.